THE ROLE OF WORK AND LABOUR MARKET FLEXIBILITY IN WORKING LIFE PROLONGATION: CASE SLOVENIA - Klemen, SIROK; Laura-Maria, DIACONESCU (Strategii Manageriale, 2014)
Building upon the premise that the prolongation of working life presents an adequate approach to address the fast approaching challenges of population ageing, the paper presents labour market outcomes of older workers in Slovenia in order to explore the role of social system and labour market flexibility in retirement behaviour. By applying bivariate graphic analysis and series of logistic models, paper finds that decisions of older workers (aged 50 - 69) of whether to retire or to continue working up to legal retirement age is being predominately shaped by the pension system parameters. Economic activity beyond this age (or when retired) on the other hand predominately correlates with flexible work arrangements and work motivation. Thus, the future policies in Slovenia aiming to prolong working careers within formal or informal sector should simultaneously do both; change pension system parameters and significantly expand the system flexibility stimulating willing and capable elderly to continue working within the formal sector.